Mine planning best practice at Kinross Gold. (1st June 2013) - Henderson, R; Turek, C
Abstract : Mine planning is the foundation of value for a mining company. Good mine planning requires solid understanding of the ore body, rigorous standards and processes, robust and useful information technology and skilled people. Life-of-Mine planning is the key to identifying strategic direction for any mine and short range mine planning is the key to delivering forecast and budget expectations. Mine planning at Kinross Gold Corporation has been identified as a critical success factor and initiatives are being prepared to improve the quality of our plans and to build bench strength in our teams. The 'Kinross Way for Mine Planning' (KWMP) has been developed and implemented to establish standards to ensure a strong business foundation. This paper briefly describes the process used to develop the KWMP and presents a selection of mine planning best practice initiatives at Kinross mines up to 2012.